Existence of a fixed point and stability results for contractive mappings on metric spaces with graphs - Reich, Simeon; Zaslavski, Alexander J. (Topological Methods in Nonlinear Analysis, 2024)
It is known that a strict contraction on complete metric spaces with graphs possesses a fixed point. In the present paper we show that this property holds for mappingson complete metric spaces with graphs which are merely contractive. We also obtain some stability results.